Pandangan Fiqh Terhadap Aakad Musyarakah dan Implementasinya Pada Perbankan Syariah - Fairuz Azzahra Irsyad; Yenni Samri Juliati Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
One form of channeling funds to sharia banks is musyarakah financing, which is the most typical and attractive of sharia financing. Because this financing agreement emphasizes cooperation and fairness in carrying out joint efforts. The aim of this research is to find out how fiqh views musyarakah contracts and their implementation in sharia banking. The research method that researchers use is the literature study research method for elaboration which involves reviewing reference books, literature, encyclopedias and reports that are relevant to the issue being discussed. The results of this research show that there are several differences in the fiqh views regarding musyarakah contracts with those practiced in sharia banking, which are in the aspects of guarantees, fines (collectability), and percentage distribution of profit sharing. With this difference, it is necessary to have an in-depth understanding of musyarakah contracts from the perspective of fiqh and its practice in sharia banking.